β-Arrestins: Regulatory Role and Therapeutic Potential in Opioid and Cannabinoid Receptor-Mediated Analgesia - Raehal, Kirsten M. (Handb Exp Pharmacol, 2014)
Pain is a complex disorder with neurochemical and psychological components contributing to the severity, the persistence, and the difficulty in adequately treating the condition. Opioid and cannabinoids are two classes of analgesics that have been used to treat pain for centuries and are arguably the oldest of “pharmacological” interventions used by man. Unfortunately, they also produce several adverse side effects that can complicate pain management. Opioids and cannabinoids act at G protein-coupled receptors (GPCRs), and much of their effects are mediated by the mu-opioid receptor (MOR) and cannabinoid CB1 receptor (CB1R), respectively. These receptors couple to intracellular second messengers and regulatory proteins to impart their biological effects. In this chapter, we review the role of the intracellular regulatory proteins, β-arrestins, in modulating MOR and CB1R and how they influence the analgesic and side-effect profiles of opioid and cannabinoid drugs in vivo. This review of the literature suggests that the development of opioid and cannabinoid agonists that bias MOR and CB1R toward G protein signaling cascades and away from β-arrestin interactions may provide a novel mechanism by which to produce analgesia with less severe adverse effects.